PENGARUH BIAYA PRODUKSI, BIAYA PROMOSI DAN VOLUME PENJUALAN TERHADAP LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Noviani, Ika; Tipa, Handra (SCIENTIA JOURNAL, 2019)
This study aims toidetermine theieffect of production costs, promotionicosts andisales volume on profits in manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017. The population inithis study is aicompany found in theiconsumer goods industry sector listed on theiIndonesia StockiExchange. The samplingitechnique uses purposive sampling. Theidependent variable in this study is profit. Independentivariables include: production costs, promotionicosts and sales volume. The analyticalimethod used is a multipleilinear regressionianalysis method using SPSS (Statistical Product andiService Solution) version 22. The sample used is 40 financial reports from 8 consumptionisector manufacturingicompaniesilisted on theiIndonesia StockiExchange. The sampleican be based on the following criteria: (1) Manufacturing companies of the consumer goods industry sector listed on the Indonesia StockiExchange from 2013-2017. (2) Data taken is financial statements in rupiah. (3) Availability and completeness of data during the period 2013-2017. The results showed that productionicosts and promotion costs did not significantly influence earnings, while sales volumeihad a significant effect on earnings.